Probiotic Beverage From Pineapple Juice Fermented With Lactobacillus and Bifidobacterium Strains - Nguyen, Bao Toan; Bujna, Erika; Fekete, Noemi; Tran, Anh T. M.; Rezessy-Szabo, Judit M.; Prasad, Ram; Nguyen, Quang D. (Frontiers in Nutrition, 2019)
Pineapple is an economically significant plant and the third most important fruit crop in the tropical and subtropical regions of the world. In this study, fermentation of pineapple juice with probiotic bacteria Lactobacillus and Bifidobacterium strains as well as changes of some properties in the beverage during storage were investigated. All tested strains exhibited good growth properties on pineapple juice without supplementation of any nutrient compounds. After 24 h fermentation, the cell counts of lactobacilli passed the level of 5*109 cfu/ml, while the cell number of bifidobacteria reached a level of 109 cfu/ml. The highest volumetric productivity (3.5*108 cfu/ml*h) was observed in L. plantarum 299V. The ratios of lactic acids to acetic acids in the cases of L. plantarum 299V and L. acidophilus La5 were 5.37 and 9.91, respectively. In the case of B. lactis Bb-12, the concentrations of lactic acid and acetic acid were 6 mM and 23 mM in natural juices, and 15 and 21 mM in the case of supplementation with prebiotics at the 16th h of fermentation, respectively. Additionally, supplementation with prebiotics at the initiation of fermentation resulted 7 mM lactic acid and 23 mM acetic acid at the end of fermentation. Fructose was the most preferred sugar for both lactobacilli and bifidobacteria. Both total phenolic content and antioxidant capacity increased slightly during fermentation and dropped during the storage period. The microbial population did not change significantly during the first month of storage. After the storage period (2 months), the probiotic bacteria lost about 0.11 log cfu/ml viability after treatment with 0.3% pepsin for 135 min, and a further 0.1 log cfu/ml after treatment with 0.6% bile salts. These values were 10 times higher than data from the fresh fermented pineapple juice. Our results are very promising and may serve as a good base for developing probiotic pineapple juice.